1996
DOI: 10.1300/j069v14n04_01
|View full text |Cite
|
Sign up to set email alerts
|

Paths and Impacts in the Progressive Independence Model:

Abstract: In an attempt to reduce homelessness and substance abuse, Chicago graduates of short-term inpatient substance abuse programs who lacked domiciles were placed into one of three conditions: (1) a case management only intervention (n = 96), (2) a case management with supported housing intervention (n = 136), or (3) a control condition (n = 187) that allowed access to normal aftercare in the community. The two treatment interventions used a "progressive independence" approach, which focuses on simultaneously ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Findings suggested that the case management needed to be continuous, community-based and intensive so as to maintain and/or increase the gains achieved. For example, in Sosin and colleague's trial [51], improvements in housing stability were attributed to the case worker's advocacy for access to income benefits and help with locating housing. Not surprisingly, higher intensity case management models, which generally have lower caseloads, also include the provision of services above and beyond care coordination and incorporate outreach services, especially in the case of ICM, which is shown to have greater effects compared to other less intensive case-management models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings suggested that the case management needed to be continuous, community-based and intensive so as to maintain and/or increase the gains achieved. For example, in Sosin and colleague's trial [51], improvements in housing stability were attributed to the case worker's advocacy for access to income benefits and help with locating housing. Not surprisingly, higher intensity case management models, which generally have lower caseloads, also include the provision of services above and beyond care coordination and incorporate outreach services, especially in the case of ICM, which is shown to have greater effects compared to other less intensive case-management models.…”
Section: Discussionmentioning
confidence: 99%
“…outcomes. One trial reported a significant improvement in employment over 24 months [44], whereas four trials showed no significant difference [48,50,51,54]. While one trial suggests that SCM improves access to income assistance (p<0.05) [51], no trials on SCM measured participant income as an outcome.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, abstinence-contingent housing appears to provide greater impact on sustained abstinence than non-abstinence-contingent housing [87,88]. In the review by Hwang et al [6], the evidence supporting the effectiveness of case management on substance use was equivocal [104,105], however, interventions that included post-detoxification stabilization [106], abstinence-contingent work therapy [107], or an intensive residential treatment program [108,109] all showed significantly greater reductions in substance use than the usual care groups. These interventions all have a component of abstinence-contingency and thus are consistent with the abstinence-contingent housing interventions discussed in the current review.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of complete 1-year follow-up data for all 8 comparators raises the question of whether these 8 represent “retained clients” rather than a pseudo-random sample of entrants to more traditional programs. In the literature, retention of homeless clients in treatment programs is low (in a review of 15 different interventions, loss of 2/3 or more was typical) ( Orwin et al, 1999 ), and in the most rigorous scientific trials, addiction treatment outcomes are modest ( Milby et al, 2009 ; Orwin et al, 2005 ; Sosin et al, 1995 ). The near-perfect results among the 8 Minneapolis comparators might be due to analysis focus on persons “retained,” rather than a random sample of program entrants.…”
Section: Limitationsmentioning
confidence: 99%